Necrotizing skin and soft-tissue infections in the intensive care unit. (January 2020) - Peetermans, M.; de Prost, N.; Eckmann, C.; Norrby-Teglund, A.; Skrede, S.; De Waele, J.J.
Abstract: Background: Necrotizing skin and soft-tissue infections (NSTI) are rare but potentially life-threatening and disabling infections that often require intensive care unit admission. Objectives: To review all aspects of care for a critically ill individual with NSTI. Sources: Literature search using Medline and Cochrane library, multidisciplinary panel of experts. Content: The initial presentation of a patient with NSTI can be misleading, as features of severe systemic toxicity can obscure sometimes less impressive skin findings. The infection can spread rapidly, and delayed surgery worsens prognosis, hence there is a limited role for additional imaging in the critically ill patient. Also, the utility of clinical scores is contested. Prompt surgery with aggressive debridement of necrotic tissue is required for source control and allows for microbiological sampling. Also, prompt administration of broad-spectrum antimicrobial therapy is warranted, with the addition of clindamycin for its effect on toxin production, both in empirical therapy, and in targeted therapy for monomicrobial group A streptococcal and clostridial NSTI. The role of immunoglobulins and hyperbaric oxygen therapy remains controversial. Implications: Close collaboration between intensive care, surgery, microbiology and infectious diseases, and centralization of care is fundamental in the approach to the severely ill patient with NSTI. As many aspects of management of these rare infections are supported by low-quality data only, multicentre trials are urgently needed.